On the Discrete Nonlinear Hammerstein Systems With Non-symmetric Kernels - Dedagić, Fehim (Sarajevo Journal of Mathematics, 2024)
We study the nonlinear Hammerstein system x(t)=_s=1^∞ k(s,t) f(s,x(s))+g(t)(tN) with non-symmetric kernel k(s,t). 2000 Mathematics Subject Classification. 47H30, 47H17